24/7 Presence of Medical Staff in the Labor Ward; No Day-Night Differences in Perinatal and Maternal Outcomes. Issue 11 (November 2017) - Tavares, Sara; Cavaco-Gomes, João; Moucho, Marina; Severo, Milton; Mateus, Mário; Ramalho, Carla; Visser, Gerard H. A.; Montenegro, Nuno
Abstract : (Abstracted from Am J Perinatol 2017;34:529–534) An unavoidable part of every health care professional's life is nighttime shifts that may have negative effects on both the providers themselves and the patients they care for. Absence of experienced staff during the night and exhaustion after long working days could lead to errors and subsequently adverse neonatal and maternal outcomes.